The value of information and communication technologies (ICT) for human development: Opportunity or threat : ¿Oportunidad o amenaza? - Del Río Sánchez, Olga (Folios, revista de la Facultad de Comunicaciones y Filología, 2012)
ICTs can represent an opportunity ( transformation potential and democratization) or a serious threat (risk of further exclusion and inequality) for the processes of human development. This paper focuses on the communicative dimension of ICTs, especially concerning the establishment and strengthening of individual and collective capacities and participation in decision making.